Round versus Anatomical Implants in Primary Cosmetic Breast Augmentation: A Meta-Analysis and Systematic Review. Issue 3 (March 2019) - Cheng, Fengrui; Cen, Ying; Liu, Chuanqi; Liu, Ruolin; Pan, Cheng; Dai, Shuiping
Abstract : Background: Choosing implant shape (round or anatomical) is one of the most essential yet controversial decisions in cosmetic breast augmentation. Many surgeons choose implant shape based on personal experience or expert opinion. This is the first systematic review and meta-analysis comparing the aesthetic effect between anatomical and round implants in primary cosmetic breast augmentation. Methods: The authors searched the PubMed, MEDLINE, Embase, ScienceDirect, Web of Knowledge, Scopus, and Cochrane Central Register of Controlled Trials databases for studies that compared anatomical and round implants in primary cosmetic breast augmentation. Primary outcomes were postoperative aesthetic effect and correct identification rate of implant shape. Random effects models were used to obtain pooled standardized mean difference and 95 percent confidence intervals. Results: One randomized comparative and four observational comparative studies met the inclusion criteria. No aesthetic superiority was found in the anatomical implant group with regard to overall appearance (standardized mean difference, 0.06; 95 percent CI, −0.40 to 0.53), naturalness (standardized mean difference, 0.18; 95 percent CI, −1.51 to 1.15), projection, upper pole contour, and lower pole contour. Pooled correct identification rate of implant shape by plastic surgeons was 52 percent (95 percent CI, 0.46 to 0.58). Conclusions: Generally, anatomical implants do not seem to have an aesthetic superiority compared to round implants. Plastic surgeons seemed to be unable to accurately differentiate the two implant shapes in vivo. Further studies should focus on identifying the specific indications for the use of anatomical implants.